Comparative study of HELLP syndrome and partial Hellp - Román Pilco, Carlos (2015)
To compare maternal and perinatal morbidity and mortality between HELLP syndrome and partial HELLP. MATERIAL AND METHODS: A prospective, descriptive study evaluating 20 cases of HELLP syndrome and 72 cases of partial HELLP in the Cayetano Heredia National Hospital between July 1991 and December 1997. RESULTS: an incidence of 3.75% was found Syndrome HELLP among patients with severe hypertension of pregnancy (533 cases), more frequently in the group of first time between 20 and 25 years (30%), 35% without prenatal care and 70% preterm birth, 70% of cesarean sections, perinatal mortality eight cases (40%), 70% of SGA infants and 30% of depressed RN. Of patients with HELLP syndrome convulsed 65% and 6 patients died (30%), causes of kidney failure, brain damage, bleeding and infection. In partial HELLP an incidence of 13.5% was found, most often in patients between 20 and 25 years. 16.7% without prenatal care, 59.7% of preterm birth, cesarean 83.4%, 21% of perinatal mortality, 58.1% PEG. RN 27% depressed. He convulsed 37.5% of mothers and maternal deaths was 1.4%. CONCLUSION: The clinical characteristics of partial HELLP HELLP syndrome did not differ fundamentally, but maternal and perinatal mortality was much higher in the former.